Perancangan UI/UX Website UPT Bahasa menggunakan Heuristic Evaluation dan User-Centered Design: Designing UI/UX of UPT Bahasa Website using Heuristic Evaluation and User-Centered Design - Mentari E.M. Pangkey; Xaverius B. N. Najoan; Sary D. E. Paturusi (Universitas Sam Ratulangi, 2024)
Abstract — In the continuously evolving digital era, websites have become a crucial platform for conveying information and interacting with users. Ensuring optimal user experience on websites is an increasingly emphasized aspect. User experience encompasses how users interact with a website and perceive their experience while using it. Currently, the Language Center at Sam Ratulangi University has not yet adopted Heuristic Evaluation and User Centered Design. In light of this issue, this research aims to enhance the quality of the user interface (UI) and user experience (UX) on the Language Center's website at Sam Ratulangi University using the Heuristic Evaluation method with a User Centered Design approach, focusing on a case study of the Language Center's website. Through the application of heuristic evaluation and user centered design, this research successfully redesigned the UI/UX for the Language Center's website. With a SUS score of 99 for the Remote test and 95.50 for the In Person test, a significant improvement in UI/UX is evident. This supports the vision of creating a more effective and efficient digital environment for the learning process and interaction between the institution and users. Keywords— Heuristic Evaluation; Language Center User Centered Design; UI/UX; Website; Abstrak — Dalam era digital yang terus berkembang, website telah menjadi salah satu platform yang sangat penting dalam menyampaikan informasi dan berinteraksi dengan pengguna. Untuk memastikan bahwa pengalaman pengguna pada website optimal, menjadi aspek yang semakin diperhatikan. Pengalaman pengguna mencakup bagaimana pengguna berinteraksi dengan website dan merasakan pengalaman saat menggunakannya. Website UPT Bahasa UNSRAT saat ini belum mengadopsi Heuristic Evaluation dan User Centered Design. Berdasarkan permasalahan tersebut maka dibuatlah penelitian ini yang bertujuan untuk meningkatkan kualitas antarmuka pengguna (UI) dan pengalaman pengguna (UX) pada website UPT Bahasa UNSRAT menggunakan metode Heuristic Evaluation dengan pendekatan User Centered Design dengan studi kasus website UPT Bahasa UNSRAT. Melalui penggunaan metode heuristic evaluation dan user centered design, Penelitian ini berhasil merancang kembali UI/UX untuk website UPT Bahasa UNSRAT. Dengan skor SUS sebesar 99 untuk Remote test dan 95.50 untuk In Person test, peningkatan yang signifikan dalam UI/UX dapat diidentifikasi, mendukung visi untuk menciptakan lingkungan digital yang lebih efektif dan efisien untuk proses pembelajaran dan interaksi antara lembaga dan pengguna. Kata kunci — UI/UX; UPT Bahasa; Situs Web; Evaluasi Heuristik; User Centered Design;